3x+12-5*5=22

Simple and best practice solution for 3x+12-5*5=22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+12-5*5=22 equation:


Simplifying
3x + 12 + -5 * 5 = 22

Multiply -5 * 5
3x + 12 + -25 = 22

Reorder the terms:
12 + -25 + 3x = 22

Combine like terms: 12 + -25 = -13
-13 + 3x = 22

Solving
-13 + 3x = 22

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 3x = 22 + 13

Combine like terms: -13 + 13 = 0
0 + 3x = 22 + 13
3x = 22 + 13

Combine like terms: 22 + 13 = 35
3x = 35

Divide each side by '3'.
x = 11.66666667

Simplifying
x = 11.66666667

See similar equations:

| x/2+x/3=5/6 | | -5x+2+2x=-6x+7 | | 2k-22=8(K+1) | | (15n)+4=36 | | 17.1d=18d+17.19 | | 2n/5-6/13=74/65 | | 8x/9-5=59 | | 4(2x-7)-2=4(x-2)+6 | | .35c+9.99=11.74 | | 6.6h-7.15-16.2h=-6.6h+19.25 | | 0=-x^2+2x+6 | | 4(2x-7)-2=4(x-3)+6 | | 9.99p+.35=11.74 | | 8k-3=3-8k | | 36c^2-121g^2=0 | | x/3-2=-8 | | x^2+3x-43=0 | | y=-x^2+2x+6 | | 4x+14=6x+7 | | -5x+2+2x=6x+7 | | 38=-2(24-x)+3(x-3) | | x^3+4x^2+36x+144=0 | | 4s^2+20st+25t^2=0 | | X^2-18x+56= | | 5d+8=33 | | -2+a=15 | | 38=-2(24-x)+3(x+3) | | -0.8x=7.2 | | 36c^2-84c+49=0 | | 14=2(e+1) | | -0.8x=72 | | 6x+15x=x |

Equations solver categories